CALCULATION OF VOLUMETRIC HYDRAULIC DRIVES AND JUSTIFICATION OF THEIR DESIGN (Web of Technology: Multidimensional Research Journal, 2024)
A number of machines and equipment are now widely used in mining, construction and agriculture with hydraulic systems. In order to increase the stable and reliable operation of hydraulic systems of these machines, it is important to calculate their volumetric hydraulic drives and justify their design, this article considers the basics of calculating volumetric hydraulic drives and designing them.